PENGEMBANGAN MODUL BERBASIS METODE DISCOVERY LEARNING UNTUK PEMBELAJARAN MENULIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 3 BUKITTINGGI - Sari, Silvia Permata (RC-INSTITUT, 2018)
This research base on problem in writing short stories text in school. That problem is the students lack the resources to learn about the short story text material for use only textbooks that students are not varied references to increase students understanding of the text write short stories. In addition, teaching materials such as textbooks have not been able to meet the learning needs of students so that learning activities are carried out less than optimal. Therefore it is necesssary to develop a module as one of the teaching materials to solve these problems. This study was conducted to describe the process of developing a module based discovery learning method in teaching writing short stories text class XI SMA/MA. The Subjects were students of class XI MIA 5 SMAN 3 Bukittinggi. Type of the research is the development (Research and Development)  of the model development 4-D. The results showed that learning to write short stories by using a model based discovery learning method for students in grade XI MIA 5 SMAN 3 Bukittinggi is valid, practical and effective. It can be seen on the validity module 91,31% with very valid criterion. Value of the practicalities of the modul by a teacher for 91,18% with very practical category, while the practicalities  of the modules by students by 92,04% with very practical categories. Effectiveness assessment module comprises the overall attitude to the value of 90 is predicated excelent, overal knowledge assessment with the value 3,41 with predicate B+. Short story writing skills ssessment text as a whole with the value of 3,34 with the predicate B+.